THE EFFECT OF SOME VARIABLES OF PRIVATE BANKING ACTIVITY ON THE EFFECTIVENESS OF LOCAL INVESTMENTS IN IRAQ: THE UNITED BANK FOR INVESTMENT AS A MODEL - Prof Dr. Subhi Hassoon; Hussein Kadhim (American Journals, 2022)
Banking activity is no longer confined to a narrow scope by a group of dealers, but rather has become a daily process that is cared for by a wide range of individuals and institutions, and its importance is increasing day after day due to the changes in the economy under which the banking sector has become the main role in preparing the appropriate conditions. Which opens the way for the economy to develop in a state characterized by a kind of stability, so it is not possible to neglect the role played by banking activity in light of an internal openness to the market economy. Investment programs, and in the context of this problem, was the United Bank for Private Investment an appropriate role in financing local investments? Was the United Bank for Private Commercial Investment a contribution to the total private fixed capital formation? Does the United Bank for Commercial Investment invest its money in specific projects?The research stems from a basic hypothesis that: The role of the private commercial bank is not insignificant in enhancing the effectiveness of local investments in a way that reduces the burden on government commercial banks. However, his role is still limited to financing these local investments and raising their effectiveness.
Keywords: Bank Activity, local investments, and The United Bank for Investment.